Activity Test of Combination of Binahong Leaf Extract (Anredera Cordifolia) and Lemongrass Extract (Cymbopogon citratus) as Antifungal Againt Pityrosporum ovale - Panji Wahlanto; M. Fadil Ramadhan (Ad-Dawaa : Journal of Pharmacy, 2023)
Pityrosporum ovale is a microorganism thought to be the main cause of dandruff. Binahong and lemongrass are herbal plants that can cure various diseases. Based on usage empirical leaf binahong and lemongrass kitchen nutritious for remove dandruff, hair loss, diabetes mellitus, anti- cancer and treatment on infection skin caused by bacteria nor mushrooms. Binahong leaf extract and extract lemongrass contain metabolites secondary wrong only flavonoids. Flavonoids are effective as antimicrobials. Destination from study this The purpose of this study was to determine the antifungal activity of the combination of binahong leaf extract (Anredera cordifolia) and lemongrass extract (Cymbopogon citratus) against Pityrosporum ovale . This study used 5 test groups, which consisted of a combination group of binahong leaf extract and lemongrass F1 = concentration 50%:50%, F2 = concentration 37,5%:12,5%, F3 = concentration 25%:25% and F4 = concentration 12,5%:37,5%, and the control group was positive (ketoconazole 2%) and negative ( aquadest), with 3 repetitions. The materials used in this study were binahong leaf simplicia and kitchen lemongrass simplicia macerated using 70% ethanol solvent, resulting in a thick extract which was then tested for antifungal activity against Pityrosporum ovale by the method diffusion paper disc on Sabouraud Dextrose Agar medium . The parameter observed was the diameter of the growth inhibition zone of the fungus Pityrosporum ovale . Analysis using ANOVA (Analysis of Variance). The results of this study were binahong leaf extract and kitchen lemongrass extract positive containing flavonoid compounds. The combination of binahong leaf extract and citronella extract has the ability to inhibit the growth of the fungus Pityrosporum ovale with visible inhibition zones formed. The most effective concentration to inhibit the growth of the fungus Pityrosporum ovale was at a concentration of F1 = 50%:50% of 17.40 mm with a strong category.